Managing System Of Diesel Fuel Provision By Mapping Fisherman Activities - Po Abas Sunarya; Reynoldus Andrias Sahulata (Universitas Raharja, 2022)
The certainty of getting diesel fuel oil for the purposes for fishing of fishermen needs to get serious attention from the government, this is due to the many irregularities seen in the fishermen's field before going to sea, to get diesel must deal with the availability of diesel with an affordable price level especially for fishermen who use fishing vessels with volumes of up to 30GT (Gross Ton) must deal with individuals who regulation seaworthy letters that ignore Article 86 of the Minister of Marine Affairs and Fisheries Regulation No. 30 of 2012 concerning Capture Fisheries Business in the Republic of Indonesia's Fisheries Management Area Indonesia is in the form of a Fishing License (SIPI) and a Fishing Vessel License (SIKPI), an Original Operation Feasibility Certificate (SLO) and an Original Sailing Certificate (SPB), which makes it difficult to obtain subsidized diesel fuel that fishermen should have with vessel qualifications up to 30GT. For this reason, the researchers built of arrangement for computerized fishermen's diesel fuelsupply so that the certainty of the availability of diesel fuel in accordance with its designation can be ensured, because all supply and distribution of diesel fuel is regulated to be carried out computerized.